Technological Determinism in Practice: A Case Study of Media Monitoring Tools in Government Public Relations - Inas Ulfa Hapsari; Novia Anggi; Irwansyah Irwansyah (Dinasti Publisher, 2026)
This study aims to explore how the use of media monitoring technology by the Public Relations (PR) department of the Ministry of State Secretariat of the Republic of Indonesia represents technological determinism in the context of government communication. The research approach used is descriptive qualitative with a constructivist paradigm, through case studies, observations, document studies, and in-depth interviews with senior public relations officers at the Ministry of State Secretariat of the Republic of Indonesia. The findings reveal that the implementation of artificial intelligence (AI)-powered media monitoring tools has significantly transformed PR workflows. AI technology facilitates accelerated issue monitoring, policy recommendation development, and enhanced strategic communication effectiveness. However, the validity of AI-generated data necessitates human interpretation and analysis to ensure accurate decision-making. This study asserts that technology is not merely an assistive tool but also a force that shapes organizational behavior. Within the framework of technological determinism, AI-driven media monitoring becomes an entity that contributes to shaping the direction of government communication systemically and structurally.